Kemiskinan dan Kesenjangan Ekonomi Rumahtangga Transmigran di Propinsi Sumatera Selatan - M Yamin (Jurnal Dinamika Sosial Ekonomi, 2002)
This research objective is to know about the income contribution, risk level of getting drop under poverty line, gap and the tolerance of household income from being poor under poverty line. The research are that is selected purposively in general pattern of transmigration program in wet land and dry land.  Beside, it is also classified into the settlement age that is 1-4 years (training term) 5-7 years (transition term) and 8 years or more (independent). The sample is taken randomly in each rural. The method of analysis using the statistical and mathematical Mesurement to answer the research objective.The result of this research showed that in the beginning term is that the biggest contribution comes from the transmigrans who work in the off farm in every kind of land. The comparison of the transmigran's househould income contribution to the age of settlement is that the more the age of settlement is that the more the age of sttlement, the more proportion of farm effor of crop. Previously, there are some household that are categorized into the poor, whether there are not poor but it is possible for them to be poor again. Comparing to the age of settlement if is has more there will be the more the survived households and the less the poor household. The rapidity of increasing the transmigran's household income is different each other, there are some that is fast, low and satable to get out from the poverty. However, in average the transmigran's household in every kind of land tends to be relatively safe.Key word : Poverty, gap, transmigration, household